KAZGUU LIBRARY VIRTUAL ASSISTANT CHATBOT - Tazhbagambetov, Daulet; Mukhametzhan, Nurbol; Dauletkhan, Abylay; Khalelov, Akberen; Kazybekov, Yersin (Nazarbayev University School of Engineering and Digital Sciences, 2024)
As an age of technologies is getting closer to reshaping daily life and services, there have been a lot of considerations for using AI and machine learning in many sectors. This project presents a virtual KazGUU library assistant which is going to be designed to enhance the user experience with complex data processing. The main objective of this project is to improve the quality of the chatbot and allow many services for users to have specialized requests and help from the AI-designed assistant so that it will be both accurate and elaborate. Primarily, the chatbot needs a convenient interface for the user so that there will not be any ergonomic inconveniences and challenges, that’s why the design aspect is one of the most important parts. On top of that, for the chatbot system to generate accurate responses, we plan to implement Artificial Intelligence and machine learning, hence making it able to respond with quality answers and current information. The system should be maintained so that it will be able to operate 24/7 and should not be vulnerable to any kinds of wrong responses and errors. For the bot to respond to current events in the library or new rules, it should be updated easily by the library staff so that it would not be a problem for them. The project is also aimed at the implementation of machine learning based on the library database, with constant updates and availability for the library portal user. There is also an application of voice-to-text and vice versa functionality for user convenience as the chat will be able to read the voice lines and produce audio outputs. Additionally, the chatbot works with the standardized chat system animations and design so that it would be familiar for the user to send text messages seamlessly as it was a conversation with a real person in a regular chat.
Keywords: AI; Chatbot; Library; Type of access: Restricted